Pests of Australian dairy pastures: distribution, seasonality and potential impacts on pasture production. Issue 4 (8th September 2021) - Umina, Paul A; Kemp, Stuart; Babineau, Marielle; Maino, James L; Roberts, Isobel; Govender, Alana; McDonald, Garrick; Popay, Alison J; Hume, David E; Hardwick, Scott; Richards, Nicola K; Reynolds, Olivia; et al.
Abstract: The dairy industry provides an important contribution to the Australian economy, but its productivity relies on grass pastures that suffer significant damage from invertebrate pests. Managing these pests remains a challenge as information on their abundance and impact is only available for a handful of taxa in a few Australian dairy regions. In this study, we undertook an extensive survey of above‐ and below‐ground pest communities across seven dairy regions in south‐eastern Australia by repeatedly sampling 57 paddocks in 2017 and 2018. We then applied energetic models to estimate the amount of metabolisable energy produced by pastures that are potentially consumed by pests. Our survey indicates that dairy farmers encounter a similar composition of above‐ground pests in most sampled regions, with a few pests, especially Sminthurus viridis (lucerne flea) and Rhopalosiphum padi (bird cherry‐oat aphid), dominating pest communities. Below‐ground pests were more variable between regions and are more likely to require region‐specific control strategies. Our energetic modelling suggests that pests consume a threefold greater percentage of metabolisable energy produced by pastures during autumn than spring. S. viridis and R. padi were among the most economically important pests across all regions and seasons, while other pests, including several species of scarabs and the small pointed snail, Prietocella barbara, were predicted to be particularly damaging in specific regions. Together, our field survey and energetic modelling provide baseline information to assist dairy farmers manage invertebrate pests and help guide future research in the Australian dairy industry.